Nutritional And Functional Quality Evaluation Of Kundang Fruit (Bouea Macrophylla Griffith) - Rajan, Nithiya Shanmuga (2014)
Unripe and ripe Bouea macrophylla Griffith (family, Anacardiaceae) are underutilized tropical fruits which are widespread in South-East Asia as Marian plum or Plum mango, and widely cultivated in Thailand, Burma, Philippines and Mauritius. The fruits are popular as Kundang (or Setar) and almost all the parts of the plants are edible and used for various culinary purposes. The unripe kundang fruit possess higher moisture (7.16